WORK MOTIVATION EFFECT ON EMPLOYEE PERFORMANCE AT SUMBERSARI PRIMARY HEALTH CARE - I Kadek Wartana (UNG, 2022)
The performance of Primary Health Center employees can be achieved if each employee has a high motivation to complete their job in accordance with their responsibilities. This study aims to analyze how much the effect of work motivation on employee performance in Sumbersari Primary Health Center in the Parigi Moutong district. This research was a correlation study with a cross-sectional approach. The population of this study was employees who work at the Sumbersari Primary Health Center in Parigi Moutong district, as many as 64 people, while the sample is all population (total population). Data were analyzed using multiple linear regression. The results showed that the effect partially works on motivation and employees performance in the Sumbersari public health center show that the salary was a variable that most significantly affects partially the employee's performance, where the t value (3,220) is greater than the t table (1,674) and The effect of overall work motivation variable influence simultaneously on the employee's performance because the value of F count larger than F table with R-value of 0,490, which means the degree of influence between variables that are strong enough. In conclusion, there was a significant influence of work motivation (salary and interpersonal relationships) on employee performance at Sumbersari Primary Health Center. The influence of motivation on employee performance was quite strong.